Synthesis of 14-Substituted-14H-Dibenzo[a,j]Xanthene Derivatives in Presence of Effective Synergetic Catalytic System Bleaching Earth Clay and PEG-600 - Sandeep T. Atkore (MDPI AG, 2021)
The synthesis of 14-aryl 14H-dibenzo[a,j]xanthenes is achieved by a simple condensation reaction between β-naphthol with aryl or alkyl aldehydes in an effective synergetic catalytic system created by combining basic bleaching earth clay and PEG-600. The advantages of the present method include catalyst recyclability, superior product yield, a shorter reaction time and the avoidance of hazardous reagents. Synthesized xanthene derivatives were also screened for their antibacterial activity against Staphylococcus aureus (MTCC 96) and Pseudomonas aeruginosa (Wild).